Developing a composite index for intrapreneurial orientation in small and medium-sized enterprises: a comprehensive dual methodology - Natividade, J.; Ferreira, F.; Zopounidis, C.; Pereira, L.; Çipi, A.; Ferreira, J. (Journal of the Operational Research Society, 2021)
Intrapreneurship has long been recognised as a way to develop competitive advantages. This is particularly evidente in small and medium-sized enterprises (SMEs), so the intrapreneurial orientation (IO) of these companies should be evaluated from multiple perspectives. Research on this topic involves a wide variety of elements that not only have a direct impact on intrapreneurial behaviour but also change over time. Nonetheless, the development of a holistic system for evaluating IO in SMEs appears to be of great interest to academics and practitioners. Based on the epistemological convictions embodied in multiple criteria decision analysis (MCDA), this study sought to combine cognitive mapping techniques and the Choquet integral (CI) to develop a new IO evaluation system for SMEs. To this end, a panel of experienced decision makers with expertise in the subject under analysis was recruited. The results of a practical application of the proposed evaluation system and composite index were validated both by the panel members and a board member of the Entrepreneurship and Innovation Department of the Portuguese Institute for the Support of Small and Medium-Sized Enterprises and Innovation (in Portuguese, Instituto de Apoio às Pequenas e Médias Empresas e à Inovação (IAPMEI)). The contributions and limitations of the proposed dual methodology are also discussed.